Continuing the journey of leadership: song of degrees. - Davis BL (ABNF Journal)
The author discusses how her experiences at Project LEAD have improved her ability to be an effective administrator and faculty member through her 'songs of degrees.' She discusses her journey as an African American leader and how the principles learned in Project LEAD impacted her leadership style and ability to collaborate with peers and colleagues. Leaders who spoke during workshops provided blueprints for mentoring and discussed the journeys of notable leaders, which provided attendees with insights into the successes and challenges of leadership. During Project LEAD, Dr. Hattie Bessent focused upon five leadership principles and applied Structural, Human Resource, Political, and Symbolic Frames. The author determined she primarily used the Structural and Political Frames after studying the frames of Bolman and Deal (2003) discussed by Dr. Bessent. The Project LEAD model focused allowed her to grow as a mentor and guided mentees to the successful completion of projects.